2002
DOI: 10.1016/s0304-3959(01)00430-4
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative back pain is associated with diverse manifestations of central neuroplasticity

Abstract: Increased or decreased gain in central nervous system processing after surgery, i.e. neuroplasticity, may play an important role in postoperative pain. Identification of patient subgroups particularly vulnerable to either type of post-surgical neuroplasticity is thus of interest. Preoperative pain has also been suggested to increase vulnerability to post-surgical chronic pain complications due to central facilitation. To study if back pain preoperatively is associated with differences in central sensory proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 33 publications
5
47
1
2
Order By: Relevance
“…Increased pain sensitivity outside the areas of clinical pain has been reported for other regional pain syndromes, such as tension-type headache (50), temporomandibular disorder (51,52), and localized trapezius myalgia (18). Our findings are also consistent with those of other studies that have demonstrated lowered pain thresholds in patients with low back pain (53) and lowered thresholds in patients with regional or widespread pain who do not have the 11 tender points required for the diagnosis of fibromyalgia (54).…”
Section: Augmented Pain Processing In Idiopathic Chronic Low Back Painsupporting
confidence: 91%
“…Increased pain sensitivity outside the areas of clinical pain has been reported for other regional pain syndromes, such as tension-type headache (50), temporomandibular disorder (51,52), and localized trapezius myalgia (18). Our findings are also consistent with those of other studies that have demonstrated lowered pain thresholds in patients with low back pain (53) and lowered thresholds in patients with regional or widespread pain who do not have the 11 tender points required for the diagnosis of fibromyalgia (54).…”
Section: Augmented Pain Processing In Idiopathic Chronic Low Back Painsupporting
confidence: 91%
“…The present study mainly discusses nociceptive/inflammatory pain. Chronic pain is more complex than acute pain as extensive short-term and long-term plastic and sometimes permanent changes (including peripheral and/or central hyperexcitability/sensitization) of the pain transmission system can occur at different levels (Kuner, 2010;Reichling & Levine, 2009) and by the modification of psychological (e.g., attentional, emotional, and anticipation status) and context factors (Grachev et al, 2000;Hunt & Mantyh, 2002;Petersen-Felix & Curatolo, 2002;Schmidt-Wilcke, 2008;Wilder-Smith et al, 2002;Woolf & Salter, 2000). Different structures in the brainvaguely labelled as the pain matrix (Iannetti & Mouraux, 2010;Lee & Tracey, 2010;Legrain et al, 2011) -are dynamically involved in processing of nociception and pain (including emotions, cognitions, and motivation) (Ossipov et al, 2010).…”
Section: Neurobiological Alterations In Chronic Painmentioning
confidence: 99%
“…The descending supraspinal control includes a dynamic balance between inhibiting and facilitating mechanisms that can be altered due to behavioural, emotional, and pathological states (Heinricher et al, 2009;Ossipov et al, 2010). When the system shifts towards inhibition, hyposensibility or lack of pain in spite of inputs from peripheral tissue may result (Heinricher et al, 2009;Kuner, 2010;Porreca et al, 2002;Ren & Dubner, 2002;Robinson & Zhuo, 2002;Wilder-Smith et al, 2002). The evolutionary value of this is that the organism can ignore pain during critical situations, e.g., flight or fight scenarios (Kuner, 2010).…”
Section: Neurobiological Alterations In Chronic Painmentioning
confidence: 99%
“…Cette douleur est souvent chronique (plus d'un an dans 35,6 % des cas) et est associée à une douleur postopératoire plus intense, comme cela a été montré dans d'autres travaux. On a ainsi démontré que la douleur préopératoire est prédictive des consommations de morphiniques en période postopératoire [26] ou que le type de douleur préopératoire est prédictif de l'existence d'une hyperalgésie postopératoire [32]. L'impact de la douleur préopératoire sur le développement d'une DCPC a été décrit pour la douleur postamputation chez l'enfant [16] et après chirurgie mammaire [17].…”
Section: Facteurs Prédictifs Liés à La Chirurgieunclassified